Analisis strategi pemasaran CV. Gema Nusa berdasarkan metode SWOT - Al Hakim, Humairoh (Nur Science Institute, 2022)
This study's purpose was to analyze CV's internal and external conditions. Gema Nusa Klaten by using a SWOT analysis and making a proposal for the business development plan of CV Gema Nusa Klaten. This study used qualitative descriptive research with in-depth interviews for data collection. The analysis technique used is SWOT analysis. Based on the SWOT analysis results, CV Gema Nusa Klaten is in a growth-oriented strategy stage. This stage is a very favorable situation where the company has the strength to take advantage of existing opportunities. The strategy applied is SO (Strengths-Opportunities), which is a strategy that supports aggressive policies. The strategy undertaken is to recruit freelance workers for sales in the regions, increase the company's production capacity, increase teamwork capabilities, increase the number of products produced, and obtain sponsorship at certain events.